Health-related quality of life and associated factors among people living with HIV/AIDS in Sichuan, China: A cross-sectional study - Zhong, Hua; Wei, Fuling; Song, Yuqing; Chen, Hong; Ni, Zhao (Frontiers in Public Health, 2023)
Purpose: This study aimed to explore health-related quality of life (HRQoL) and its associated factors among people living with HIV/AIDS (PLWHA) in Sichuan, China. Methods: A total of 401 PLWHA were recruited from the city of Panzhihua between August 2018 and January 2019. Demographics characteristics and disease-related data were collected by self-administered questionnaires. Health-related quality of life (HRQoL) was measured by the medical outcome study HIV health survey (MOS-HIV), which measured ten sub-dimensions and two summarized dimensions, physical health summary score (PHS) and the mental health summary score (MHS). Logistic regression models were used to explore the variables independently associated with quality of life. Results: The PHS and MHS measured by MOS-HIV were 53.66±6.80 and 51.31±7.66, respectively. Age, residence, educational level, methadone use, residence, CD4 lymphocyte counts, symptoms counts and BMI were significantly affected the patients’ HRQOL in the univariate χ2-test analysis. Education level(P=0.002) was found to be a significant influence on patients' quality of life, both in physical health and mental health dimensions. Age(P=0.032), CD4 lymphocyte counts(P=0.007), symptoms counts (P<0.001) and BMI level(P<0.001) were positively related with PHS of quality of life in the multivariable logistic regression model. Conclusion: The HRQoL of PLWHA in the Sinchuan province was relatively low. Age, residence, educational level, methadone use, residence, CD4 lymphocyte counts, symptoms counts and BMI were positively related with quality of life. This study indicates that health care providers need to provide more care and supports to PLWHA, especially for these with lower education level, unhealthy body mass index, more symptomatic presentation and older age．